324 Increased cervical strength is associated with reduced head impact magnitude in international blind football. (3rd March 2020) - Fitzpatrick, Daniel; Thompson, Peter; Kipps, Courtney; Webborn, Nick
Abstract : Background: Blind Football has the highest rate of injury of any Paralympic sport. Head injuries, including concussion, represent a large proportion of these injuries. Blind athletes are less able to anticipate impacts. It has been shown in other sports that athletes with greater neck strength are better able to resist head impacts in a laboratory, and that they are less likely to sustain a concussion. Objective: To establish whether isometric neck strength influenced head impact forces in Blind Football. Design: Observational study. Setting: International Blind Football training and matches over six-months. Patients (or Participants): England Blind Football squad (7 males, mean age 28.6y) Interventions (or assessment of risk factors): Isometric neck strength was measured once during preseason using a hand-held dynamometer. Head impact data was recorded using a head mounted accelerometer and gyroscope (GForce Tracker) attached to player's mandatory blindfolds. Main outcome measurements: Head impact location (front, back, left or right) was recorded. Linear regression was performed to compare mean linear acceleration and rotational velocity to isometric cervical strength (flexion, extension, left lateral flexion and right lateral flexion) with movements paired to the impact direction they oppose. Results: A total of 212.5 player hours were recorded (192.5 hours in training and 20 hours in matches). Increased cervical strength was associated with reduced mean linear acceleration (R 2 =0.1912, p=0.020) when comparing opposing movement to respective impact location. There was no association between cervical strength and rotational velocity (R 2 =0.001, p=0.861) or between number of impacts (R 2 =0.4354 p=0.1068). Conclusions: Elite Blind Football players with greater cervical strength were subject to head impacts with smaller linear acceleration. This is consistent with existing research in able-bodied athletes and provides an additional factor of the live game play setting in Blind Football. Further research is required to determine if cervical strength training can reduce the risk of concussion in Blind Footballers.